Eu(III) local coordination in white light emitters organic-inorganic hybrids. - Carlos, L. D.; Ferreira, RAS; Bermudez, V. D.; Bueno, L. A.; Molina, C.; Messaddeq, Y.; Ribeiro, SJL (Soc Brasileira Quimica, 2001)
Eu3+ luminescence and EXAFS (Extended X-ray Absorption Fine Structure) results are presented for organic-inorganic hybrid gel hosts composed of a siliceous network to which small chains of oxyethylene units are covalently grafted by means of urea bridges. Coordination numbers for Eu3+ ions range from 12.8 to 9.7 with increasing Eu3+ concentration while the Eu3+-first neighbours mean distance is found to be constant at 2.48-2.49 A in the same concentration range. Emission spectra display a broad band in the green/blue spectral region superposed to narrow lines appearing in the yellow/red region in such a way that for the eyes emission appears white. The broad band is assigned to intrinsic NH groups emission and also to electron-hole recombination in the nanosised siliceous domains. The narrow lines are assigned to intra-4f(6), D-5(0)--> F-7(0-4) Eu3+ transitions and from the energy position of the F-7(0-4) levels a mean distance could be calculated for the Eu3+-first neighbours. The calculated results are in good agreement with the experimental ones obtained from EXAFS analysis.
Keywords: organic-inorganic hybrids; luminescence; EXAFS